The Application of Passive Vibroprotective Systems Having Power Characteristics with Hysteresis Loops of Rectangular Shape for the Main Pumping Units. (2017) - Tokarev, Artem; Zotov, Alexey; Valeev, Anvar
Abstract: The causes of large vibrations of main pump units piping and its influence to the level of the pump unit oscillations are analyzed. The source of increased vibration exposure in the "pump - pipe" system is often not only the pump unit, but pump piping also. Piping of the pumping unit in case of its operating parameters changing can be entered to resonance. It is considered the reasons and oscillation magnitude of the booster pump NMP 5000-90 and its piping. Application of different types of vibration isolators is analyzed in terms of their effectiveness and the amount of force transmitted to the foundation. Special attention is paid for vibration isolators having force characteristics with hysteresis loops of rectangular shape that have high efficiency.